Teachers’ Knowledge and Usage of Ethnomathematics in Asokwa Municipality (Kumasi) of Ashanti Region of Ghana - Seth Kwame Osei; Ebenezer Bonyah; Yarhands D Arthur (RIRAI Publisher, 2023)
This study investigated teachers’ knowledge and usage of ethnomathematics in Asokwa Municipality (Kumasi) in the Ashanti region of Ghana. The triangulation design of the mixed method was used. Purposive sampling was used to select all the 62 mathematics teachers from all the public junior high schools in the municipality. Results from the data analysis showed that mathematics teachers in Asokwa Municipality possess a high level of knowledge of ethnomathematics, with an overall mean score of 3.68 and a standard deviation of 0.61. The study recommended that Ghana Tertiary Education Commission (GTEC) should ensure that teachers’ colleges of education train mathematics teachers on the integration of ethnomathematics in the teaching of mathematics